Does Job Insecurity Deteriorate Health? A Causal Approach for Europe - Eve Caroli; Mathilde Godard (Institute for the Study of Labor (IZA), 2014)
This paper estimates the causal effect of perceived job insecurity i.e. the fear of involuntary job loss on health in a sample of men from 22 European countries. We rely on an original instrumental variable approach based on the idea that workers perceive greater job security in countries where employment is strongly protected by the law, and relatively more so if employed in industries where employment protection legislation is more binding, i.e. in industries with a higher natural rate of dismissals. Using cross-country data from the 2010 European Working Conditions Survey, we show that when the potential endogeneity of job insecurity is not accounted for, the latter appears to deteriorate almost all health outcomes. When tackling the endogeneity issue by estimating an IV model and dealing with potential weak-instrument issues, the health-damaging effect of job insecurity is confirmed for a limited subgroup of health outcomes, namely suffering from headaches or eyestrain and skin problems. As for other health variables, the impact of job insecurity appears to be insignificant at conventional levels.
Keywords: I19; J63; 330; job insecurity; health; instrumental variables